The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1128/jvi.79.5.2823-2830.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibody-Dependent Complement-Mediated Inactivation of both Autologous and Heterologous Virus in Primary Human Immunodeficiency Virus Type 1 Infection

Abstract: Specific CD8 T-cell responses to human immunodeficiency virus type 1 (HIV-1) are induced in primary infection and make an important contribution to the control of early viral replication. The importance of neutralizing antibodies in containing primary viremia is questioned because they usually arise much later. Nevertheless antienvelope antibodies develop simultaneously with, or even before, peak viremia. We determined whether such antibodies might control viremia by complement-mediated inactivation (CMI). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 37 publications
6
90
0
Order By: Relevance
“…Thus, unlike neutralizing Ab, which is largely isolate specific, high-avidity Ab may be capable of blunting acute viremia for a diversity of isolates. This is consistent with studies on Fc-and complement-mediated virolysis and cytolysis that have demonstrated that patient serum mediating these activities recognizes a range of Envs (1,2,5,12,18,32,35). Our studies also show that not all clade B Envs elicit high-avidity Ab for incident clade B isolates.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, unlike neutralizing Ab, which is largely isolate specific, high-avidity Ab may be capable of blunting acute viremia for a diversity of isolates. This is consistent with studies on Fc-and complement-mediated virolysis and cytolysis that have demonstrated that patient serum mediating these activities recognizes a range of Envs (1,2,5,12,18,32,35). Our studies also show that not all clade B Envs elicit high-avidity Ab for incident clade B isolates.…”
Section: Discussionsupporting
confidence: 76%
“…The correlation held for the avidity of the Ab at the time of challenge as well as the avidity of the Ab at 3 weeks postchallenge. We suggest that avidity correlated with protection because it facilitated the initiation by bound Ab of Fc-mediated mechanisms of viral control such as complement-mediated lysis (1,14,35), antibody-dependent cellular cytotoxicity (2,8,12,30,37), antibody-dependent cell-mediated virus inhibition (11), and phagocytosis. Presumably the more tightly Ab bound to Env on virions and infected cells, the more effective it was at initiating Fc-mediated mechanisms of virus control.…”
Section: Discussionmentioning
confidence: 99%
“…3). These endogenous anti-HIV-1 Abs developed by HIV-1-infected individuals in both the acute and chronic phases of infection activate complement through the classical pathway, as indicated by published reports that C1q-deficient serum as a source of complement fails to induce anti-HIV-1 Ab-mediated virolysis (45). Fig.…”
Section: Discussionmentioning
confidence: 83%
“…In the context of HIV infection, antibody (Ab)-dependent cellular cytotoxicity (ADCC) independently correlates with differences in HIV disease course (14). Levels of Abs that are able to activate NK cells to mediate ADCC are elevated in the plasma of subjects who have nonprogressive disease and are diminished in subjects with progressive infection (2,14,15,30,43) and are detectable as early as a few weeks postinfection (1,13). Interestingly, Hessell et al demonstrated a critical role of ADCC in the protection of monkeys from infection following passive infusion of the neutralizing Ab B12 lacking the capacity to engage Fc receptors, suggesting that ADCC may play a critical role in protection from both disease acquisition and progression (21).…”
mentioning
confidence: 99%